2016
DOI: 10.1111/aos.13289
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of antioxidative factors related to AMD risk development in the polish patients

Abstract: In conclusion, our data showed that insufficient antioxidant capacity may have an important role in age-related macular degeneration. The polymorphism of GPx Pro197Leu may reduce the ability to scavenge free radicals in retina and contribute to the development of AMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
1
17
1
1
Order By: Relevance
“…First, we assessed the systemic levels of components of the antioxidant system in peripheral blood and found that the activity of the majority of tested substances were significantly increased in patients with AMD (GPx, R-GSSG, and GSH transferase levels in RBCs and SOD, CAT, GPx, and R-GSSG levels in PLT), whereas only the CAT activity in RBC was evidently reduced in patients with AMD compared with controls. Our observation of increased GPx activity is in contrast to the results reported by Mrowicka et al [ 44 ] and Plestina-Borjan et al [ 31 ], where significantly lower GPx (RBC) activity was observed in AMD patients in comparison with controls. On the other hand, in the large POLA study of a cohort of 2584 participants, the increased levels of plasma GPx concentration, which catalyses H 2 O 2 degradation by GSH, correlated with a nine-fold increase in the prevalence of late AMD [ 45 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…First, we assessed the systemic levels of components of the antioxidant system in peripheral blood and found that the activity of the majority of tested substances were significantly increased in patients with AMD (GPx, R-GSSG, and GSH transferase levels in RBCs and SOD, CAT, GPx, and R-GSSG levels in PLT), whereas only the CAT activity in RBC was evidently reduced in patients with AMD compared with controls. Our observation of increased GPx activity is in contrast to the results reported by Mrowicka et al [ 44 ] and Plestina-Borjan et al [ 31 ], where significantly lower GPx (RBC) activity was observed in AMD patients in comparison with controls. On the other hand, in the large POLA study of a cohort of 2584 participants, the increased levels of plasma GPx concentration, which catalyses H 2 O 2 degradation by GSH, correlated with a nine-fold increase in the prevalence of late AMD [ 45 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Similar to SOD, CAT function decreases in the macular and peripheral RPE with ageing [ 58 ], but in contrast to SOD, CAT immunoreactivity is reduced in RPE cells in the eyes of patients with and without AMD [ 47 , 59 ]. Our finding of reduced CAT activity in patients with AMD is consistent with previous reports [ 44 ]. As proposed by Tate et al, treatment with ROS-generating compounds induces CAT expression in RPE cells, which protects against H 2 O 2 , even in the adjacent RPE cells without upregulated CAT expression.…”
Section: Discussionsupporting
confidence: 93%
“…First, oxidative stress is a well-established mechanism that contributes to cellular dysfunction/cell death, including photoreceptor death. Oxidative stress has been reported in development and acceleration of many retinal diseases, including retinitis pigmentosa (11,15,52,79), AMD (80)(81)(82), glaucoma (83)(84)(85), and diabetic retinopathy (86,87). Second, TH has a profound effect on mitochondrial function/metabolic homeostasis.…”
Section: Th Signaling Suppression-induced Cone Protection Involves Thmentioning
confidence: 99%
“…While exogenous micronutrient supplementation protective role has been unequivocally demonstrated in the landmark AREDS and AREDS2 studies (Age-Related Eye Disease Study Research Group 2001, Age-Related Eye Disease Study 2 Research Group 2013), interestingly, not only prevention but also visual function may be improved by supplementation, with a clinical trial using antioxidant supplementation in an Italian population having shown improved visual acuity (VA) and contrast sensitivity (Piermarocchi et al 2012). While not much is known regarding naturally occurring dietary nutrients and their role as a modifiable risk factor, insufficient antioxidant capacity may have an important role in AMD (Mrowicka et al 2017). In our exploratory analysis, we have targeted those micronutrients more frequently described in the literature.…”
Section: Dietary Micronutrientsmentioning
confidence: 99%